PEMANFAATAN HUTAN PINUS MOTILANGO SEBAGAI KAWASAN EKOWISATA BERBASIS MASYARAKAT - Ariawan Ariawan; Jupri Jupri; Frengki Eka Putra Surusa (Jurnal Abdi Insani, 2022)
Motilango Pine Forest is a natural resource that is able to provide economic value to the surrounding community. Mtoilango pine forest has another potential in the form of natural beauty that has not been utilized as a source of income for the community. To increase the utilization of the Motilango pine forest as a tourist destination that has a tourist attraction, it must meet the criteria of Attraction, Accessibility, Ancilary service, Community. This activity aims (a) To realize the Motilango pine forest into a tourist destination to improve the welfare of the people around the area. (b). Fulfillment of the criteria for tourist destinations that have tourist attractions and their management based on the concept of Community Based Tourism (CBT). The method used in this service activity uses the Focus group discussion method, training and counseling, as well as simulation and practice. The focus group discussion was attended by partners, namely the Pinus Jaya Sejahtera Cooperative and the village government and the Motilango village community agreed on the formation of a tourist destination with the name Motilango pine ecotourism, and succeeded in arranging an ecotourism committee in charge of managing and working in the manufacture of tourism support facilities. Furthermore, training and counseling are carried out by the service team so that partners, village government and youth organizations as well as the community to understand the legal aspects and utilization of forest areas produce a group that is aware of the motilango village tourism. Simulation and practice in determining the zoning of the use of the Pinus Motilango Ecotourism area in the form of a regional master plan design. The achievement of this activity is the availability of a master plan that can be used as a guide in the development and utilization of Pine Ecotourism. In the end, this service succeeded in realizing a tourist destination in the form of Pinus Motilango Ecotourism and the fulfillment of community-based ecotourism criteria that could improve the welfare of the community.